PENERAPAN MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK KELAS XI MIPA SMA NEGERI 3 PADANG - Niakmatul Husni (Departemen Matematika, 2022)
Mathematical literacy abilities are important abilities for students to solve daily problems and develop their mathematical ability. Then, the students need to have mathematical literacy ability because this ability is one of the national focuses in the future in assessing the quality of education in schools. But, in reality the students of class XI MIPA at SMA Negeri 3 Padang have low mathematical literacy ability. The effort that can be made to improve that ability of students are to apply Realistic Mathematics Education model. The type of the research is quasy experiment research with non-equivalent posttest only control group design. Results showed that mathematical literacy ability of students that apply Realistic Mathematics Education model is better than mathematical literacy ability of students that apply conventional learning. Moreover, the mathematical literacy ability of students that apply Realistic Mathematics Education model has increased significantly.Keywords– mathematical literacy ability, realistic mathematics education, conventional learning